2021
DOI: 10.1101/gr.276025.121
|View full text |Cite
|
Sign up to set email alerts
|

Genomic environments scale the activities of diverse core promoters

Abstract: A classical model of gene regulation is that enhancers provide specificity whereas core promoters provide a modular site for the assembly of the basal transcriptional machinery. However, examples of core promoter specificity have led to an alternate hypothesis in which specificity is achieved by core promoters with different sequence motifs that respond differently to genomic environments containing different enhancers and chromatin landscapes. To distinguish between these models, we measured the activities of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…A remarkable result, obtained independently by Bergman et al [12] and Hong et al [27], is that promoters and enhancers generally act multiplicatively on transcriptional input. We asked whether Enformer qualitatively captured the same rule.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A remarkable result, obtained independently by Bergman et al [12] and Hong et al [27], is that promoters and enhancers generally act multiplicatively on transcriptional input. We asked whether Enformer qualitatively captured the same rule.…”
Section: Resultsmentioning
confidence: 99%
“…To further probe the ability of Enformer to correctly account for distal sequence context in its predictions, we used TRIP (thousands of reporters integrated in parallel) sequencing data compiled by Hong et al [27]. In this experiment, six different short promoter fragments were integrated at thousands of locations across the genome and then their activity at each location was measured.…”
Section: Current Deep Models Mostly Cannot Predict the General Impact...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our assays were performed using a reporter plasmid library and it is known that the genomic environment affects the absolute level of transcription. Based on prior results, it is likely that the absolute but not relative expression level of UAS-core combinations is partially dependent on chromatin 40,49 , so use of the reporter likely does not affect conclusions on functional compatibility and coactivator…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…We next focused on the behavior of the most highly specific UASs. For the small subset of UASs that display highly biased expression at CR core promoters Prior work demonstrated that inducible metazoan core promoters tend to exhibit lower intrinsic activity than constitutive core promoters 40,41 . To test if this feature is conserved in yeast, we examined whether CR promoters display low intrinsic activity, given that CR genes, like metazoan inducible genes, tend to be stress responsive and are enriched for TATA-containing promoters.…”
Section: Differences In Regulation Between Tfiid and Cr Promotersmentioning
confidence: 99%